2011
DOI: 10.5012/bkcs.2011.32.12.4454
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photoluminescence of GdVO4:Eu Nanophosphors for Flexible and Transparent Displays

Abstract: Europium ion doped metal orthovanadate (MVO 4 :Eu, M = Y, Gd, La) has been widely used as commercial red-emitting phosphors in cathode ray tubes (CRTs), and fluorescent lamps, 1,2 with photoluminescence quantum yields of up to 95%.3,4 Commercial micron-sized MVO 4 :Eu phosphors are generally prepared by high-temperature solid-state reactions. However, these micron-sized phosphors cannot be used in flexible and transparent displays due to their high scattering. Because nano-sized materials do not show any scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As a typical host sensitizing PL material, GdVO4:Eu 3+ shows the character that its emission intensity and efficiency mainly depend on the host absorption and energy transfer from the host to activators. From the literature, 17,18 it has been reported that Gd 3+ ions in the host lattice increase their absorption of VUV/UV excitation energy, and change the crystal eld of the host lattice. Should the increase of PL intensity be ascribed to the absorption increase of Gd 3+ ions?…”
Section: Resultsmentioning
confidence: 99%
“…As a typical host sensitizing PL material, GdVO4:Eu 3+ shows the character that its emission intensity and efficiency mainly depend on the host absorption and energy transfer from the host to activators. From the literature, 17,18 it has been reported that Gd 3+ ions in the host lattice increase their absorption of VUV/UV excitation energy, and change the crystal eld of the host lattice. Should the increase of PL intensity be ascribed to the absorption increase of Gd 3+ ions?…”
Section: Resultsmentioning
confidence: 99%
“…GdVO 4 :Eu 3+ NPs have been successfully synthesized via a facile solvothermal route 4 8 , a urea hydrolysis method 9 , a co-precipitation synthesis 10 , as well as facile hydrothermal methods 11 12 . Using these methods, tetragonal particles (d ~ 70 nm), spherical particles (d ~ 40 nm), ellipsoid particles (d ~ 20 nm, l ~ 25 nm), nanorods (d ~ 5 nm, l ~ 20 nm), and nanowires (d = 15 nm, l = a few microns) were fabricated 8 9 10 11 12 . Submicronic polyhedrons with formula GdVO 4 :RE 3+ (RE 3+ = Sm 3+ , Dy 3+ , Er 3+ ) (d ~ 300 nm) were obtained by facile hydrothermal methods 13 .…”
mentioning
confidence: 99%
“…Thus, the adopted synthetic procedure should guarantee a precise control over the particles' dimensions. Several synthetic strategies have been proposed for the preparation of GdVO 4 nanoparticles doped with rare earth ions, including sol-gel 32 , urea hydrolysis 33 , electrospinning 34 , and hydro/solvothermal methods 35,36 . Inagaki et al developed a synthesis to obtain GdVO 4 :Nd/Yb nanoparticles with an homogenous dimensional distribution (around 20 nm), but this approach requires a complex microreaction method followed by an autoclave treatment 25 .…”
Section: Introductionmentioning
confidence: 99%